POTENSI DAN KENDALA SISTEM RESI GUDANG (SRG) UNTUK MENDUKUNG PEMBIAYAAN USAHA PERTANIAN DI INDONESIA (Forum Penelitian Agro Ekonomi, 2024)
Price fall of agricultural commodities usually taking place during harvest season adversely affect the farmers. The government addresses this issue through launching the Warehouse Receipt System (SRG). This paper critically reviews potencies and constraints of WRS in supporting agricultural finance and its improvement measures. Theoretically, SRG provides potential benefits, especially in financial support, stabilizing price fluctuation, increasing farmers’ income, credit mobilization, improving product quality, etc. However, SRG implementation in the agricultural sector encounters a number of constraints, such as high transaction costs, inconsistency of quantity and quality of agricultural products, lack of bank support, and weak farmers’ institutions. Since the farmers’ institutions are not well organized yet, SRG procedures seem very complicated and need simplification. In addition, SRG promotion and more conducive government policy are also necessary to optimize this credit scheme.
Keywords: warehouse receipt system; agricultural commodities; agricultural finance; government policy; Indonesia; sistem resi gudang; komoditas pertanian; pembiayaan pertanian; kebijakan pemerintah